Evaluating self-reported psychopathy and associations with personality traits outside the WERID countries: evidence from two Arabic speaking Middle Eastern countries - Megreya, Ahmed M. (Mental health, religion & culture, 2023)
The prevalence, manifestation and assessment of psychopathy might be influenced by culture. However, the vast majority of research on psychopathy has been carried out in a few Western, Educated, Industrialized, Rich and Democratic (WEIRD) countries. In contrast, there is limited knowledge in the Middle Eastern Arabic speaking countries for psychopathy. A large sample of under-graduate university students (N = 850) from two Arab countries (Egypt and Kuwait) administered the original version of the Levenson Self-Report Psychopathy Scale (LSRP) along with the NEO-Five Factor Inventory (NEO-FFI). The LSRP is better organized using a three-factor structure (Egocentrism, Callousness, and Antisocial) rather than its original two-factor model (primary and secondary psychopathy) and the reliabilities of all factors were found to be acceptable to high. In addition, all factors correlated negatively with agreeableness, conscientiousness, and extraversion but positively with neuroticism. These results provide initial evidence for cross-cultural similarity of psychopathy construct.